Digital visualization of quality data in final demands station - Chowda Shetty, Madhusudhan; Johansson Billskog, Kevin (My University, 2020)
To have better customer satisfaction, high quality of the product is necessary to compete on the market. Many automotive industries use perceived quality to maintain their global market value. With ever-increasing competition on the market, industries tend to move towards mass customization which involves digitization, better visualization and automation too in their process. This thesis discusses the process of arranging standardized specifications data to an evaluated visualization device which will support the current process, by creating better circumstances for the operators from a cognitive ergonomics point of view and finally stating that having the visualization aid in the process helps the inexperienced operators and other parts of the work task. The research begins with a basic literature study followed by a structured work procedure to meet the objectives and demands set for the thesis, which was done by answering framed research questions. After the literature study, the research is followed by the screening process consisting of a current state analysis and an identification of limitations with observations and interviews with operators working in the observed work station. Some evaluation methods were used to select a suitable visualization aid with regards to the identified information. The next phase is the testing phase, which involves the evaluation and testing of the newly developed solution. Finally, the implementation of the developed program with the visualization device was introduced to the process. These obtained results were compared with the older results to finalize the main objective of the thesis and point out the differences per the operator’s feedback which was obtained. These results pointing out that their is an requirement of cognitive support in the process and it having it does improve the process and also possible recommendations in the future.
Keywords: Perceived Quality, Digitalization, Visualization, Cognitive Ergonomics; Final Demands Station, Implementation